Researching theories of crime and deviance - Kubrin, Charis Elizabeth (Oxford University Press, 2009)
Introduction -- Rational choice and deterrence theories -- Trait theories -- Social disorganization theory -- Anomie and strain theories -- Social learning theories -- Control theories -- Labeling theory -- Conflict theory -- Integrated theory -- Conclusion